1994
DOI: 10.1111/j.1365-3180.1994.tb01967.x
|View full text |Cite
|
Sign up to set email alerts
|

Cycloxydim absorption by suspension‐cultured velvetleaf (Abutilon theophrasti Medic.) cells

Abstract: Summary: Résumé: Zusammenfassung The influence of several experimental parameters (time, concentration, pH, and temperature) on cellular absorption of cycloxydim was studied using suspension–cultured velvetleaf (Abutilon theophrasti Medic.) cells. Cycloxydim and its metabolites accumulated in cells to a concentration higher than that of the external medium. Metabolism was rapid with 88.6 % conversion to metabolites within 6 h. Cycloxydim absorption was linearly related to the external cycloxydim concentration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[53], and Echinochloa colona (L.) Link [54] increased. Temperature also influenced 14 C-glyphosate absorption by cultured velvetleaf cells [55]. Nearly twice as much glyphosate was absorbed at 28°C than at 4 or 16°C.…”
Section: Resultsmentioning
confidence: 97%
“…[53], and Echinochloa colona (L.) Link [54] increased. Temperature also influenced 14 C-glyphosate absorption by cultured velvetleaf cells [55]. Nearly twice as much glyphosate was absorbed at 28°C than at 4 or 16°C.…”
Section: Resultsmentioning
confidence: 97%
“…Translocation could also be improved by increasing the uptake of glyphosate into the symplast. In cell culture, AMS increases the permeability of the cell membrane to ions30, 34 and can enhance cellular uptake of several herbicides, including glyphosate, imazethapyr and cycloxydim 35–37. It is important to point out, however, that other studies using isolated cells have found no effect of AMS on glyphosate uptake across the plasmalemma 38, 39.…”
Section: Discussionmentioning
confidence: 98%